Aristotle's Explanationist Epistemology of Essence. (26th November 2019) - Hauser, Christopher
Essentialists claim that at least some individuals or kinds have essences. This raises an important but little-discussed question: how do we come to know what the essence of something is? This paper examines Aristotle's answer to this question. One influential interpretation (viz., the Explanationist Interpretation) is carefully expounded, criticized, and then refined. Particular attention is given to what Aristotle says about this issue in DA I.1, APo II.2, and APo II.8. It is argued that the epistemological claim put forward in DA I.1 differs from that put forward in APo II.2 and II.8, contrary to what has been claimed by Explanationists, and that each of these distinct epistemological claims rests on a distinct non-epistemological thesis about essence. Consequently, an 'Enriched Explanationist Interpretation' is developed which takes into account both of the aforementioned elements in Aristotle's epistemology of essence. The paper concludes by highlighting an insight the preceding exegetical discussion offers to contemporary essentialists seeking to explain how we come to know what something's essence is.